A phase I study of high-dose rosuvastatin with standard dose erlotinib in patients with advanced solid malignancies - Goss, Glenwood D. (J Transl Med, 2016)
BACKGROUND: Synergistic cytotoxicity with high-dose statins and erlotinib has been demonstrated in preclinical models across a number of tumour types. In this phase I study, we evaluated the safety and potential anti-tumour activity of escalating doses of rosuvastatin in combination with the standard clinical dose of erlotinib in heavily pretreated patients with advanced solid tumours. METHODS: This was a single-center, phase I open-label study to determine the safety and recommended phase two dose (RPTD) of rosuvastatin in combination with 150 mg/day standard dose of erlotinib. Using a 3 + 3 study design and 28-day cycle, escalating doses of rosuvastatin from 1 to 8 mg/kg/day ×2 weeks (cycle 1) and 3 weeks (subsequent cycles) given concurrently with erlotinib were evaluated. In order to expand the experience and to gain additional safety and pharmacokinetic data, two expansions cohorts using concurrent or alternating weekly dosing regimens at the RPTD were also evaluated. RESULTS: All 24 patients enrolled were evaluable for toxicity, and 22 for response. The dose-limiting toxicity (DLT) of reversible muscle toxicity was seen at the 2 mg/kg/day dose level. Maximal tolerated dose (MTD) was determined to be 1 mg/kg/day. Thirty-three percent of patients developed at least 1≥ grade 2 muscle toxicity (rhabdomyolysis: 1/24, myalgia: 7/24) resulting in one study-related death. Durable stable disease for more than 170 days was seen in 25 % of patients that received concurrent treatment and were evaluable for response (n = 16). Plasma erlotinib levels on study were unaffected by the addition of rosuvastatin. CONCLUSIONS: The observed disease stabilization rate of 25 % with combination therapy in this heavily pretreated population is encouraging, however, the high levels of muscle toxicities observed limited this combination strategy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12967-016-0836-6) contains supplementary material, which is available to authorized users.